Implementasi Virtual Chatbot pada Portal Website Merdeka-FILKOM menggunakan HubSpot - Muhammad Fadhel Aribowo; Herman Tolle; Fais Al Huda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The merdeka-filkom website portal, which is a website aims to be a forum for students to share their experiences of Independent Learning activities, and as an information center for Independent Learning activities at the Merdeka Campus at the Faculty of Computer Science, Universitas Brawijaya. Limited working time and personnel, so that the provision of information becomes slow and reduces the user experience on the website portal. To overcome these problems, building a robot in the form of a chat service to make it easier for users to find information and stakeholders of the Merdeka-Filkom website in conveying information on the Merdeka-Filkom Website Portal using HubSpot will greatly facilitate users and application developers. The design is carried out using the Human-Centered Design method and then evaluates the design with usability testing with an effectiveness level of 99% and an efficiency of 95%, also tests the usability scale system to measure the level of user satisfaction with a score of 79.4 with an adjective rating of good.